PENGARUH RASIO KEUANGAN TERHADAP PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN - Sabella, Adinda; Januarti, Indira (Department of Accounting, Faculty of Economics & Business, Universitas Diponegoro, 2021)
This study is aims to examine the effect of financial performance of Corporate Social Responsibility disclosure. The dependent variable used in this study is CSR Diclosure and independent variable is financial performance as measured by profitability, liquidity, and leverage. This population in this study is all Indonesia companies that received ASSRAT award in the period 2018-2019. This research sample was selected with certain criteria. Based on criteria, samples used was 30 companies in 2018, and 29 companies in 2019, with a total sample of 59 samples. The method of analysis used in this research is Partial Least Square (PLS) analysis. The result of this study indicate that liquidity and leverage have a negative significant effect on CSR disclosure. While, profitability is not significantly influence the CSR disclosure.